Voces poéticas de la periferia: la poesía de Alessandro Buzo como articuladora de una comunidad alternativa de cuidado - Jorge Ignacio Cid Alarcón (Caravelle)
This article reflects on the recent productions of marginal peripheral literature, particularly the case of the poetry of Alessandro Buzo’s poetry in light of the notions of the abject as a matrix of segregation (Kristeva, Butler), fear as political affection (Safatle), community (Bauman) and care communities (Butler), in order to evaluate its poetics as a critical articulating tool of an alternative care community.